A Time‐Resolved Cryo‐EM Study of Saccharomyces cerevisiae 80S Ribosome Protein Composition in Response to a Change in Carbon Source. Issue 2 (2nd December 2020) - Sun, Ming; Shen, Bingxin; Li, Wen; Samir, Parimal; Browne, Christopher M.; Link, Andrew J.; Frank, Joachim
Abstract: The role of the ribosome in the regulation of gene expression has come into increased focus. It is proposed that ribosomes are catalytic engines capable of changing their protein composition in response to environmental stimuli. Time‐resolved cryo‐electron microscopy (cryo‐EM) techniques are employed to identify quantitative changes in the protein composition and structure of the Saccharomyces cerevisiae 80S ribosomes after shifting the carbon source from glucose to glycerol. Using cryo‐EM combined with the computational classification approach, it is found that a fraction of the yeast cells' 80S ribosomes lack ribosomal proteins at the entrance and exit sites for tRNAs, including uL16(RPL10), eS1(RPS1), uS11(RPS14A/B), and eS26(RPS26A/B). This fraction increased after a change from glucose to glycerol medium. The quantitative structural analysis supports the hypothesis that ribosomes are dynamic complexes that alter their composition in response to changes in growth or environmental conditions.